LiCl as Phase‐Transfer Catalysts to Synthesize Thin Co2P Nanosheets for Oxygen Evolution Reaction. Issue 9 (14th September 2018) - Pan, Zhiming; Niu, Pingping; Hou, Yidong; Fang, Yuanxing; Liu, Minghui; Wang, Xinchen
Abstract: Inorganic salts have been widely studied as templates for the synthesis of 2D layer structures. However, these salts normally can only serve as templates without any catalytic activity. Here, we report that LiCl used for the synthesis of ultrathin nanosheets not only serves as template for the synthesis of ultrathin Co2 P nanosheets with a thickness of 0.7 nm but also acts as a catalyst that induces the phase‐transfer from CoP to Co2 P. The Co2 P nanosheets have a high electrochemical performance for oxygen evolution reaction. Abstract : Transfer market of salt : LiCl not only serves as template to synthesize ultrathin Co2 P nanosheets with a thickness of 0.7 nm but also acts as catalyst to induce phase transfer from CoP to Co2 P that has a high electrochemical performance for the oxygen evolution reaction.